MBOT News: WTC Red LIPS Mentorship Program - Kamalrudin, Massila (Malaysia Board of Technologists (MBOT), 2023)
The Malaysia Board of Technologists (MBOT) is promoting women in technology through the WTC Red LIPS Mentorship Program, which is part of its Woman Technologist Chapter (WTC) initiative. The program, which includes eight prominent figures and women members of MBOT, aims to address the unique challenges faced by women in the tech industry by providing a supportive platform for networking, mentoring, and knowledge-sharing. The mentors include CEOs of MMC Oil & Gas Engineering, Hengyuan Refining Company Berhad, Tenaga Nasional Berhad, and PETRONAS Global Technical Solutions. Board members Ts. Dr. Mahaletchumy Arujanan and Assoc. Prof. Ruslinda binti A. Rahim also serve as mentors. The event attracted 100 participants from diverse technology fields in both government and private sectors.